Penerapan Akhlaq dalam Dunia Bisnis: Studi Kasus pada Perusahaan Syariah - Kusyana, Kusyana; Romlah, Romlah (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2023)
This research aims to examine the application of akhlaq in the business world through a case study of Sharia-compliant companies. Akhlaq, encompassing moral and ethical values in Islam, is a fundamental basis in the business practices of Sharia-compliant companies. This study employs a qualitative approach with a case study method to understand how akhlaq values are implemented in daily operations and their impact on company performance. The findings indicate that the application of akhlaq in Sharia-compliant companies not only enhances employee satisfaction and loyalty but also strengthens relationships with customers and other stakeholders. Moreover, the implementation of akhlaq significantly contributes to achieving long-term sustainable business goals. This study provides deep insights into the importance of integrating akhlaq values in business practices and how it can bring significant benefits to Sharia-compliant companies.